Chapter 3 Thematic Mapping of Kaebyok and the Rise of the Prophetic Critic - Lee, Jae-Yon (Taylor & Francis, 2023)
Chapter 3 examines the formation of the "prophetic critic" in Kaebyŏk (The opening, 1920- 1926) through distant reading. As the most influential intellectual magazine of the 1920s, Kaebyŏk introduced various social ideas of Marxism, social reform, and humanitarianism into Korea's religious thought. Thus, this chapter analyses the digitalized version of the magazine through quantitative approaches to word-frequency and co-occurring words; in particular it employs topic modelling. Because it assigns topics by measuring the probability of keywords rather than simply locating co-occurring words, topic modelling reveals how different topics are semantically interrelated in a larger text. With this method, Chapter 3 examines the interplay between topics of art and literature and society-related themes such as nation, economic classes, and social reconstruction. It pays particular attention to the two topics of saengmyŏng (vitality) and saenghwal (ways of living or livelihood) to examine how Korean writers articulated a proto-type of Marxist realism (saenghwal) out of romanticism (saengmyŏng). In the end, Chapter 3 argues that Kaebyŏk shaped the "prophetic critic" who preemptively combined religious, social, and literary worldviews of the future to create the guiding principles for the realist fiction that would dominate the latter half of the 1920s.